Alcohol Consumption and Interpersonal Injury in a Pediatric Oral and Maxillofacial Trauma Population: A Retrospective Review of 1, 192 Trauma Patients. Issue 2 (June 2015) - McAllister, Peter; Laverick, Sean; Makubate, Boikanyo; Jones, DavidCarl
The social, financial, and health implications of adult alcohol-related oral and maxillofacial trauma have been recognized for several years. Affordability and widespread accessibility of alcohol and issues of misuse in the pediatric trauma population have fostered concerns alcohol may be similarly implicated in young patients with orofacial trauma. The aim of this study was to review data of pediatric facial injuries at a regional maxillofacial unit, assess the prevalence of alcohol use, and review data of patients sustaining injury secondary to interpersonal violence. This study is a retrospective, 3-year review of a Regional Maxillofacial Unit (RMU) trauma database. Inclusion criterion was consecutive facial trauma patients under 16 years of age, referred to RMU for further assessment and/or management. Alcohol use and injuries sustained were reviewed. Of 1, 192 pediatric facial trauma patients, 35 (2.9%) were associated with alcohol intake. A total of 145 (12.2%) alleged assault as the mechanism of injury, with older (12–15 years) ( n = 129; 88.9%), male ( n = 124; 85.5%) ( p < 0.001) patients commonly involved and alcohol use implicated in 26 (17.9%) presentations. A proportion of vulnerable adolescents misuse alcohol to the risk of traumatic facial injury, and prospective research to accurately determine any role of alcohol in the pediatric trauma population is essential.